Perbandingan Efisiensi dan Kapasitas Baterai Sepeda Motor Jenis Lithium Iron Phosphate (LifePO4), Lithium-Ion (Li-Ion) , dan Lead Acid - Kurniawan Dwi Sa'bani; Khambali Khambali; Yuniarto Agus Winoko; Nike Nur Farida (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The development of electric motor vehicles drives the need for efficient, stable, and reliable energy storage systems. This study aims to compare the performance of three types of batteries commonly used in electric motorcycles, namely LiFePO4 (Lithium Iron Phosphate), Li-Ion (Lithium Ion), and Lead Acid (Lead Battery). The parameters tested include energy efficiency, capacity, and performance during the starting process. The test method was carried out for 60 minutes through a charging and discharging process (charge-discharge), using a pzem-015 measuring instrument and a multimeter to monitor the current, voltage, input/output power, and battery capacity. The test results show that the LiFePO4 battery provides the best performance. This battery has the highest efficiency and capacity, reaching 1430 mAh, with a stable average efficiency in the range of 50–60%. In addition, LiFePO4 also produces the highest current and voltage when used for starting, making it very reliable for the initial needs of electric motorcycle operation. Meanwhile, the Li-Ion battery recorded a high initial efficiency of up to 87.27%, but this efficiency decreased and then stabilized at 72%, with a recorded capacity of 1360 mAh. Although its efficiency is quite good, its long-term stability is still below that of LiFePO4. Meanwhile, the Lead Acid battery showed the lowest performance. Its efficiency continued to decline to only 26.3% at the end of the test. Its capacity is 1380 mAh, but the increase is unstable, indicating inconsistencies in power storage and discharge. Based on these results, LiFePO4 batteries are recommended as the main choice for electric motorcycles because they excel in aspects of energy efficiency, performance stability, and long-term durability.